PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN KEADILAN PROSEDURAL TERHADAP KOMITMEN ORGANISASI GURU SMK NEGERI DI JAKARTA UTARA - Hetiny Muthia Rahmy (Jurnal Manajemen Pendidikan, 2018)
The purpose of this research is to know the effect of Leader Member Exchange (LMX) and procedural justice toward State Vocational School teacher’s organizational commitment in North Jakarta. The research was conducted using survey method with quantitative approach and path analysis technique. The population of this research is 186 teachers. Research samples as much as 127 teachers were selected using simple random sampling technique. The data was obtained through questionnaires and analyzed using path analysis techniques. Based on the results of the data analysis in this research, it is concluded that: (1) the Leader Member Exchange (LMX) has a positive direct effect to organizational commitment; (2) the procedural justice has a positive direct effect to organizational commitment; (3) the Leader Member Exchange (LMX) has a positive direct effect to procedural justice. Therefore, the organizational commitment can be improved through the enhancement of Leader Member Exchange (LMX) and procedural justice.